PENGARUH PERLAKUAN BLANCHING TERHADAP MUTU TEPUNG GEMBILI (Dioscorea Esculenta L.) - Meily Simatupang; Jamaludin Jamaludin; Yus Witdarko (Faculty of Agriculture, Musamus University, 2021)
Gembili (Dioscorea Esculenta L.) is one of Papua's local food crops high in carbohydrates. The content of polyphenol enzymes in gembili will impact the colour quality of gembili flour. An effort to overcome this problem is to provide additional blanching treatment. This study aimed to determine the effect of blanching on the flour quality and obtain the optimal temperature and time in making gembili flour. This study uses an experimental method. The treatments given were blanching temperatures of 60℃, 65℃, 70℃, 75℃ and control for 5 minutes, 10 minutes, 15 minutes. Parameters analyzed were gembili flour yield, flour moisture content, fineness level, and whiteness degree. To determine the best treatment using the parameter ranking method. The results showed that the highest rendemen of gembili flour was at a blanching temperature of 70℃ for 5 minutes. The moisture content of gembili flour was from 8.92% to 11.70%. The fineness level of gembili flour was from 99.37% to 99.60%. The highest whiteness degree of gembili flour was at a blanching temperature of 60℃ for 5 minutes. The optimal blanching treatment was a blanching temperature treatment of 65℃ for 10 minutes.